Building Trust with All Stakeholders Is Vital for Success : Implementing a Public-Private Partnership in the Electricity Sector in Guinea - Cusiac-Barr, Elan; Boubakary, Aicha Farida; Kouassi, Ange Claver (International Finance Corporation, Washington, DC, 2016)
Fragile and conflict-affected states (FCS) face specific socioeconomic and political challenges that hinder their ability to improve infrastructure anddrive economic growth. Implementation of public-private partnership (PPP)transactions in FCS is usually hampered by weak institutional structures and capacity, limited or lacking PPP experience, and an uncertain businessenvironment complicated by fragile politics and security issues. However,it is still possible for governments to define workable and desirable PPParrangements that will help deliver public service and infrastructure improvements by attracting the necessary investments and expertise. This SmartLesson examines how IFC’s PPP Transaction Advisory group (C3P),in collaboration with the World Bank and the government of Guinea,successfully introduced an innovative PPP in Guinea’s national electricity utility by pooling World Bank Group resources and building the trust of our Guinea counterparts—and attracted private sector interest in Guinea amid ongoing political transition and a health scare from the Ebola epidemic.